2022
DOI: 10.3389/fnut.2022.850076
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of Sea-Buckthorn Procyanidins on Oxidative Injury HUVECs

Abstract: As society develops and aging populations increase, the incidence of arteriosclerosis, a seriously harmful cardiovascular disease (CVD) which mostly results from endothelial cellular oxidative damage, has continuously risen. Procyanidins from sea-buckthorn is a powerful antioxidant, although its protective effect on the cardiovascular system is not yet clearly understand. In this study, oxidative damaged HUVECs induced by palmitate acid (PA) were used as a model and the regulatory effect of procyanidins from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…They have potential therapeutic benefits in various diseases such as cerebral ischemia, Alzheimer's disease, and cerebrovascular diseases [8,26,27]. The key role of PCs in the prevention of cardiovascular and cerebrovascular diseases is their contribution to the stabilization of the antioxidant system [26]. The results of our present study revealed that PCs dramatically protected nerve function and reduced cerebral infarct volume and pathological lesions in vivo, similar to a previous report [8].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They have potential therapeutic benefits in various diseases such as cerebral ischemia, Alzheimer's disease, and cerebrovascular diseases [8,26,27]. The key role of PCs in the prevention of cardiovascular and cerebrovascular diseases is their contribution to the stabilization of the antioxidant system [26]. The results of our present study revealed that PCs dramatically protected nerve function and reduced cerebral infarct volume and pathological lesions in vivo, similar to a previous report [8].…”
Section: Discussionsupporting
confidence: 90%
“…Procyanidins (PCs) are natural biological polyphenols with the effects of anti-oxidation, anti-apoptosis, and the inhibition of inflammation. They have potential therapeutic benefits in various diseases such as cerebral ischemia, Alzheimer's disease, and cerebrovascular diseases [8,26,27]. The key role of PCs in the prevention of cardiovascular and cerebrovascular diseases is their contribution to the stabilization of the antioxidant system [26].…”
Section: Discussionmentioning
confidence: 99%
“…The research results showed H. rhamnoides L. could be used for 12 h by HUVECs and had no detectable cytotoxicity. The different concentrations of H. rhamnoides L. increased the mitochondrial membrane potential and NO level and decreased LDH leakage in a dose–effect relationship, which indicated H. rhamnoides L. improved oxidative damage …”
Section: Resultsmentioning
confidence: 85%
“…The research results showed H. rhamnoides L. could be used for 12 h by HUVECs and had no detectable cytotoxicity. The different concentrations of H. rhamnoides L. increased the mitochondrial membrane potential and NO level and decreased LDH leakage in a dose−effect relationship, which indicated H. rhamnoides L. improved oxidative damage 77. H. rhamnoides L. polysaccharide possessed moderate antioxidant activity, and its clearance rate of O 2 − • was 18.92% higher than that of V C when the polysaccharide concentration was 1200 μg/mL.…”
mentioning
confidence: 87%
“…Their antioxidant capacity is 40 times greater than that of vitamin C or E [12] . Due to their natural antioxidant properties, PACs have been suggested as a possible protector against oxidative stress damage to various organs and tissues, including the ovaries [14][15][16] . Research has shown that PACs can effectively mitigate pathological changes in granulosa cells by inhibiting autophagy and apoptosis, which ultimately contributes towards delaying ovarian aging [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%